2014
DOI: 10.1007/s10815-014-0341-x
|View full text |Cite
|
Sign up to set email alerts
|

Relative kinetic expressions defining cleavage synchronicity are better predictors of blastocyst formation and quality than absolute time points

Abstract: PurposeMorphology alone is not enough for the selection of the embryo (s) with the highest implantation potential and time-lapse imaging has added embryo development kinetics as another selection criterion. Therefore, a combination of morphology with kinetics has inspired a new field termed “morphokinetics”, providing a new way of evaluating and selecting embryos. The aim of the study was to identify a criterion solely based on morphokinetic data and available up to the 8-cell stage (t8) to predict blastocyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 32 publications
6
43
1
2
Order By: Relevance
“…In contrast, higher embryo production was obtained in autumn and spring. These results support the cleavage rate as a good predictor of the in vitro blastocyst development (Cetinkaya et al., ; Fu et al., ). Accordingly, the results show a significant decrease in cleavage rates and blastocyst production during winter, corroborating our hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, higher embryo production was obtained in autumn and spring. These results support the cleavage rate as a good predictor of the in vitro blastocyst development (Cetinkaya et al., ; Fu et al., ). Accordingly, the results show a significant decrease in cleavage rates and blastocyst production during winter, corroborating our hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…As mentioned above, longer s2 intervals (i.e., reduced synchrony) have been hypothesized to be associated to reduced implantation rates [13]. It was also observed that time intervals and relative ratios defining synchronicity are highly predictive of blastocyst development and quality [28]. Therefore, the difference in s2 emerged in our study from the comparison of embryos generated in IVM and stimulated cycles should not be overlooked but rather further investigated.…”
Section: Discussionsupporting
confidence: 50%
“…Aparicio et al claim that important improvements in embryo selection may be realized using time-lapse technology because of the possibility of selecting viable embryos with a high developmental potential [ 3 ]. Cetinkaya et al present an itemized comparative analysis of kinetic parameters focusing on relative time ratios and time intervals [ 4 ]. They produced an equation based on analyzed morphokinetic variables, allowing for the prediction of blastocyst formation.…”
Section: Introductionmentioning
confidence: 99%